A pilot, longitudinal, 24-week study to evaluate the effect of interferon beta-1a subcutaneous on changes in susceptibility-weighted imaging-filtered phase assessment of lesions and subcortical deep-gray matter in relapsing–remitting multiple sclerosis. (March 2015) - Zivadinov, Robert; Dwyer, Michael; Markovic-Plese, Silva; Hayward, Brooke; Bergsland, Niels; Heininen-Brown, Mari; Carl, Ellen; Kennedy, Cheryl; Dangond, Fernando; Weinstock-Guttman, Bianca
Background: Studies have shown a relationship between increased iron content and clinical progression, cognitive impairment, and brain atrophy in patients with multiple sclerosis. Altered phase, as determined by susceptibility-weighted imaging (SWI), can potentially capture iron content changes. Objective: The objective of this study was to investigate phase changes in white matter (WM) lesions and subcortical deep-gray matter (SDGM) of patients with relapsing–remitting (RR) MS treated with interferon beta-1a administered subcutaneously versus untreated healthy controls (HCs). Methods: We conducted a 24-week, nonrandomized, open-label pilot study of 23 patients with RRMS receiving interferon beta-1a administered subcutaneously and 15 HCs. Patients were imaged on a 3T scanner at baseline, 12, and 24 weeks; changes in phase behavior in WM lesions and regional SDGM [mean phase of low-phase voxels (MP-LPV)], and in SDGM volumes, were measured. Between- and within-group changes were tested using nonparametric statistics adjusted for multiple comparisons. Results: The number ( p = 0.003) and volume ( p < 0.001) of phase WM lesions both significantly decreased among RRMS patients over 24 weeks. At baseline, MP-LPV was lower (suggestive of greater iron content) in total SDGM among RRMS patients versus HCs ( p = 0.002). Week 24 MP-LPV changes from baseline were not significantly different between groups in total SDGM or any region except the putamen (−0.0025 radians in RRMS patients versus 0.0035 radians in HCs; p = 0.041). Conclusions: Over 24 weeks, phase lesions were reduced significantly in the RRMS group. These preliminary results suggest that SWI-filtered phase may become a useful tool for monitoring RRMS disease activity.